Commanding officers - Miller, David (David M.O.) (John Murray, 2001)
This book concentrates wholly on the all-important role of the commanding officer. There are many books which study the art of high command in war, and almost as many on individual acts of heroism. There are however few about the leadership required of the men (and in the future women) who are the most important people in the military chain of command: the commanding officers. These people - naval ship captains, army battalion commanders and air force squadron leaders - are the vital link in the chain, whose job is to ensure that higher command's orders and plans are carried out, and to react to events during the course of battle. It is on their shoulders that success or failure in the front line rests, as they make crucial decisions, frequently at very short notice, and sometimes involving major moral decisions, all amid shot, shell and confusion.;David Miller has built this book on a very large number of actual command dilemmas drawn from different countries, different periods of history, and all three arms of service. It is filled not only with analysis but also with action, often of a surprising sort.The reader finds himself, or herself, commanding a submarine, leading a bomber formation over Iraq, or dealing with ethnic hatred in the former Yugoslavia. The book has an immediacy and a realism that should absorb all readers of military history, whether they are serving officers or in command of no more than an armchair.